2020
DOI: 10.1111/1462-2920.15330
|View full text |Cite
|
Sign up to set email alerts
|

Host–microbiota interactions and responses to grass carp reovirus infection in Ctenopharyngodon idellus

Abstract: Summary Gut microbiota could facilitate host to defense diseases, but fish–microbiota interactions during viral infection and the underlying mechanism are poorly understood. We examined interactions and responses of gut microbiota to grass carp reovirus (GCRV) infection in Ctenopharyngodon idellus, which is the most important aquaculture fish worldwide. We found that GCRV infection group with serious haemorrhagic symptoms (G7s) showed considerably different gut microbiota, especially with an abnormally high ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The data revealed T to be the major environmental factor shaping the dominant microbial genera including Prochlorococcus, Chryseobacterium, Acinetobacter, Rheinheimera, Polynucleobacter, and Janthinobacterium in water column. Most of these genera mentioned were reported to be potential pathogenic bacteria [33], and Flavobacterium that was strongly correlated to SD also has been reported to be consistent of opportunistic pathogens [34][35][36], it will be an important challenge to manage the black carp pond by quickly monitoring the water temperature and SD for the future. As the more prevalent bacteria in pond water, Polynucleobacter was strongly negatively correlated to pH.…”
Section: Discussionmentioning
confidence: 99%
“…The data revealed T to be the major environmental factor shaping the dominant microbial genera including Prochlorococcus, Chryseobacterium, Acinetobacter, Rheinheimera, Polynucleobacter, and Janthinobacterium in water column. Most of these genera mentioned were reported to be potential pathogenic bacteria [33], and Flavobacterium that was strongly correlated to SD also has been reported to be consistent of opportunistic pathogens [34][35][36], it will be an important challenge to manage the black carp pond by quickly monitoring the water temperature and SD for the future. As the more prevalent bacteria in pond water, Polynucleobacter was strongly negatively correlated to pH.…”
Section: Discussionmentioning
confidence: 99%
“…Each fish gut ecosystem is colonized by a diverse community of microorganisms from the surrounding environment during food consumption ( 1 , 2 ). Mounting evidence has indicated that the composition and structure of gut microbiota in fish can vary considerably across host development ( 3 5 ), which also could be affected by numerous other factors including host immunity ( 6 ), diseases ( 7 ), diets ( 8 ), and the local environment ( 9 ). An increasing number of studies have indicated that both deterministic and neutral processes could affect the colonization of fish gut microbiota ( 4 , 10 ), which play important roles in regulating the host’s functions.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have indicated that both deterministic and neutral processes could affect the colonization of fish gut microbiota ( 4 , 10 ), which play important roles in regulating the host’s functions. For example, gut microbiota in fish have been shown to be closely involved in regulating host metabolism ( 11 ), promoting growth ( 12 ), stimulating the immune system ( 13 ), affecting tissue development ( 14 ), and defense against some diseases ( 7 ). Unfortunately, how microorganisms that have colonized the fish gut ecosystem interact with each other, and the mechanism(s) regulating gut ecosystem stability remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cetobacterium is the most abundant genus in the intestinal microbiota of most fish, and its members are involved in host metabolism and inflammation [ 68 ]. Previous studies have shown that exogenous stimuli can induce dysbiosis of the gut microbiota, and aggravate host inflammatory reactions through lipopolysaccharide-related NOD-like receptors and TLRs pathways in fish [ 69 ]. Barnesiellaceae are related to fat and energy metabolism [ 70 ].…”
Section: Discussionmentioning
confidence: 99%